MENGAPA PH KOLAM BEKAS TAMBANG RELATIF STABIL?: STUDI KASUS PADA KOLAM SURYA DAN SANGATTA NORTH DI AREAL PT KPC SANGATTA KALIMANTAN TIMUR - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2009)
This study was carried out to verified the characteristics of water void in the conservation efforts in the coal mining area. The general sipnotic surveys were conducted in Surya and Sangatta void PT Kaltim prima Coal on-9 September, 2008. The monitoring data of water pH indicated that the spatial variation inpH in both void were small. The difference in pH between the surface and bottom of void water was less than 1.3.The other parameter such as dissolved oxygen, temperature and turbidity showed that both void have a good water as a normally waters. Stability in in the water quality especially in pH would causedby a smart management in acid mine drainage effort and highly pH buffer condition in mining area.